1991
DOI: 10.1001/jama.1991.03460120059036
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Status of Patients With Angiographically Normal Coronary Arteries and Panic Disorder

Abstract: Cardiology patients with normal coronary angiography demonstrate continuing and substantial social, health, and work disability. We hypothesized that the diagnosis of panic disorder would mark those for whom continuing disability is most likely. We interviewed 72 such patients at the time of their normal angiogram, and then again an average of 38 months later. Those with panic disorder (n = 36) demonstrated significantly more disability at follow-up than did the other study patients. We conclude that those pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 32 publications
2
30
1
Order By: Relevance
“…This study examined the psychosocial status of chest pain patients who met DSM-III-R diagnostic criteria for panic 15 At follow-up, significantly more PD+ patients experienced chest pain and viewed their general health as poor relative to PD-patients. Our results are also similar to those of Roy-Byrne and colleagues, who found that at a follow-up of 4-10 months, significantly more PD+ than PD-patients demonstrated an inability to work, more frequent ED and outpatient physician visits, and higher hospitalization rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study examined the psychosocial status of chest pain patients who met DSM-III-R diagnostic criteria for panic 15 At follow-up, significantly more PD+ patients experienced chest pain and viewed their general health as poor relative to PD-patients. Our results are also similar to those of Roy-Byrne and colleagues, who found that at a follow-up of 4-10 months, significantly more PD+ than PD-patients demonstrated an inability to work, more frequent ED and outpatient physician visits, and higher hospitalization rates.…”
Section: Discussionmentioning
confidence: 99%
“…14 PD is a serious, debilitating anxiety disorder that if left untreated often has a chronic course and may lead to the development of other psychiatric conditions such as agoraphobia, depression and substance abuse disorders. [13][14][15][16][17][18] Despite the apparent psychological and psychosocial distress exhibited by these patients, most panic disorder patients go undetected/unreported by physicians. 19,20 We previously reported that 98% (106/108) of PD diagnoses go unrecognized by emergency cardiologists in a specialized chestpain assessment unit.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the outcome of these patients with regard to future cardiac events and mortality may be lower than in patients with more typical angina (20) or more acute chest pain onset (13).Whereas it may be higher than among those who have been diagnosed with NCCP based on negative angiography (15). In addition, traditional risk factors for CAD were identified at the baseline investigation in all patients and may have been treated, thus possibly decreasing the risk for future CAD development.…”
Section: External Validitymentioning
confidence: 99%
“…PD patients often relate their chest pain to heart disease (39) even after CAD is ruled out by angiography (15). The fear of having heart disease causes frequent referral to emergency departments or cardiology clinics with costly cardiological investigations as the result (11;33;35).…”
Section: Panic Disorder and Chest Painmentioning
confidence: 99%
See 1 more Smart Citation